Pendayagunaan Kewirausahaan Siswa Kompetensi Keahlian Pemasaran (Studi Kasus di SMK Sudirman 1 Wonogiri). - Titik Asmawati (Jurnal Pendidikan Ilmu Sosial, 2016)
This study aims to: (1) Describe the planning Enterprise Marketing Competency SMK Students Sudirman 1 Wonogiri. (2) Describe the implementation of Enterprise Reform Vocational Students Skills Competency Marketing Sudirman 1 Wonogiri. (3) Describe the Evaluation of Enterprise Reform Vocational Students Skills Competency Marketing Sudirman 1 Wonogiri. The approach used in this study is qualitative as a whole is expected to describe the object under study, analyze it so that it can be formulated for the appropriate utilization of entrepreneurship in creating young entrepreneurs. The Subjects were SMK Sudirman 1 Wonogiri consists Principal , Vice Principal , Head of Competence Expertise , Teacher Productive , infrastructure and written documents relating to the utilization of entrepreneurship .Methods of data collection is conducted by observation, interview and documentation study. Utilization of entrepreneurial students through several steps, namely: Preparation (Curriculum, Infrastructure, human resources and preparation of activities), Implementation and evaluation. Entrepreneurship implemented in school utilization (Unit Production and Business Center) and extramural (DU / DI) through industrial visits and apprenticeship (PSG). The role of teachers in schools as actors and designers wirausawan in schools and mentor students at DU / DI is crucial to realize the potential entrepreneurs from graduate school. Keywords: business center, production unit, PSG and reform